Natural bioactive compounds in Alzheimer's disease: From the perspective of type 3 diabetes mellitus - Huang, Juan; Huang, Nanqu; Mao, Qianhua; Shi, Jingshan; Qiu, Yu (Frontiers in Aging Neuroscience, 2023)
There is a close relationship between Alzheimer's disease (AD) and diabetes mellitus (DM), so AD is also called type 3 diabetes mellitus (T3DM). Many natural bioactive compounds have shown the potential to treat AD and diabetes. We mainly review the polyphenols represented by resveratrol (RES) and proanthocyanidins (PCs), and alkaloids represented by berberine (BBR) and Dendrobium nobile Lindl. alkaloids (DNLA) from the perspective of T3DM to review the neuroprotective effects and molecular mechanisms of natural compounds in AD.